Decision support in nuclear and radiological emergency situations: Are we too focused on models and technology?. (2nd July 2007) - French, Simon; Carter, Emma; Niculae, Carmen
The last 20 years has seen enormous advances in mathematical modelling and computing techniques. In the aftermath of the Chernobyl Accident, many of these have been incorporated in Decision Support Systems (DSS) to aid nuclear emergency management. This paper reviews what has been achieved; but it also reflects on how the tools fit into emergency management processes and discusses whether too much emphasis is being placed on the technological aspects of what is a complex, socio-technical issue.